Bunyaviruses Affect Growth, Sporulation, and Elicitin Production in Phytophthora cactorum - Poimala, Anna; Raco, Milica; Haikonen, Tuuli; Černý, Martin; Parikka, Päivi; Hantula, Jarkko; Vainio, Eeva J. (MDPI AG, 2022)
Phytophthora cactorum is an important oomycetous plant pathogen with numerous host plant species, including garden strawberry (Fragaria × ananassa) and silver birch (Betula pendula). P. cactorum also hosts mycoviruses, but their phenotypic effects on the host oomycete have not been studied earlier. In the present study, we tested polyethylene glycol (PEG)-induced water stress for virus curing and created an isogenic virus-free isolate for testing viral effects in pair with the original isolate. Phytophthora cactorum bunya-like viruses 1 and 2 (PcBV1 & 2) significantly reduced hyphal growth of the P. cactorum host isolate, as well as sporangia production and size. Transcriptomic and proteomic analyses revealed an increase in the production of elicitins due to bunyavirus infection. However, the presence of bunyaviruses did not seem to alter the pathogenicity of P. cactorum. Virus transmission through anastomosis was unsuccessful in vitro.
Keywords: mycovirus; Bunyaviridae; oomycetes; Phytophthora cactorum; virus curing; PEG 8000